Nuclear power - Metcalf, Tom.; Metcalf, Gena. (Detroit : Greenhaven Press, 2007)
Explores the advantages and disadvantages of using of nuclear power and the history of harnessing nuclear power technology.
Includes bibliographical references and index.
Keywords: Nuclear engineering -- Juvenile literature; Nuclear energy -- Juvenile literature; Nuclear engineering; Nuclear energy